The Clinical Features of Hand-arm Vibration Syndrome in a Warm Environment—A Review of the Literature - Ting, Anselm Su; Darus, Azlan; Bulgiba, Awang; Maeda, Setsuo; Miyashita, Kazuhisa (Japan Society for Occupational Health, 2012)
The internationally accepted limit values and the health effects of hand-transmitted vibration exposure have been described extensively in the literature from temperate climate countries but not from a tropical climate environment. Objectives: We conducted a systematic review of the health effects of hand-transmitted vibration exposure in tropical countries to determine the characteristics of hand-arm vibration syndrome in a warm environment and compared the findings with the results of the systematic reviews published by the US NIOSH. Methods: We searched major medical databases including MEDLINE, PubMed, Embase, CINAHL, Ovid and Cochrane based on the terms “hand arm vibration syndrome,” “hand transmitted vibration,” “vibration white finger” and “Raynaud” up to January 2011. Only studies conducted in a tropical or subtropical environment were selected for the review. The quality of the selected papers was assessed independently by two investigators using predefined criteria. A standard set of information was abstracted from the papers for review. Results: Only six papers from tropical countries and three papers from subtropical countries were available in the literature. No vibration white finger was reported in the tropical countries. Neurological symptoms were prevalent in the vibration-exposed workers. Finger coldness seems to be an important surrogate for vascular disorder in a tropical environment. Meta-analysis could not be performed due to inadequacy of the information reported in these papers. Conclusions: The current dose-response relationship in ISO5349-1 for hand-transmitted vibration exposure is not applicable to a tropical environment. Further studies on hand-arm vibration syndromes in tropical countries are needed.